Edge tracing of t-shirt by robot for spreading purposes - Sahari K.S.M.; Seki H. (2023)
Edge tracing is considered important for deformable object manipulation in order to spread and reveal the original shape of an object before it can be sorted. This paper proposes a unique tracing method for t-shirt spreading by robots. Tracing in this paper context involves tracing the edge of the t-shirt, with the robot arm movement based on feedback from sensors. Adequate force control is also applied to the tracing gripper during tracing so that it doesn't grip the fabric too hard or vice versa which can affect the performance of the robot. Vision sensor is used from time to time to check whether the tracing gripper has reached a corner or not. Based on the algorithm used for towel spreading, algorithm for edge tracing of shirt to find a second or third corner is proposed. The method is simply looking at possibilities of tracing through corners, changing tracing trajectory as well as tracing on two layers of fabric. Practical experiments were conducted to evaluate the proposed method. (2012) Trans Tech Publications, Switzerland.